On the neutrality of credit-driven asset bubbles - Christopher Phillip Reicher (Kiel Institute for the World Economy (IfW), 2011)
This paper proposes and tests a theory of credit-driven asset bubbles which are neutral in their real effects. When a lender such as a government, central bank, or banking sector is willing to lend infinitely against collateral, explosive asset bubbles can form which exactly offset a bubble in household liabilities. Surprisingly, evidence from a VAR using long-run restrictions supports the idea that asset bubbles are approximately neutral in their real effects before 2007. The evidence becomes more ambiguous if one includes post-2007 data, hinting that the post-2007 degree of comovement between asset prices and output comes from an unusual regime.
Keywords: G12; E44; E51; 330; Bubbles; fiscal theory of the price level; collateral constraints; neutrality; transversality conditions; Vermögen; Börsenkurs; Bubbles; Kredit; Kreditsicherung; Verschuldungsrestriktion; Private Verschuldung; Wohlfahrtseffekt; Theorie; Schätzung; USA